Biochar improves soil physical characteristics and strengthens root architecture in Muscadine grape (Vitis rotundifolia L.) - Chang, Yuru; Rossi, Lorenzo; Zotarelli, Lincoln; Gao, Bin; Shahid, Muhammad Adnan; Sarkhosh, Ali (Chemical and biological technologies in agriculture, 2021)
Background Biochar is widely assumed as an effective soil amendment. It improves soil structure and fertility, thereby enhancing crop growth and development. There is still a knowledge gap in research on the beneficial impact of biochar on root growth and root architecture in perennial woody plants. Therefore, in our 14-week greenhouse study, pinewood-based biochar was applied as soil amendment for muscadine grape cultivation to investigate its effects on soil physical properties and crop root growth. Muscadine grape cv. Alachua was grown on Ultisols soil mixed with five rates of biochar on weight basis. Soil mixture properties and root attributes were determined. Results The soil bulk density decreased 40% and the total porosity increased 50% by adding 20% biochar into pure sandy soil. The soil water-holding capacity (WHC) of 20% biochar amendment soil was 1.9 times as pure as sandy soil. In addition, the incorporation of biochar did not only ameliorate soil acidity at the beginning but also increased soil pH buffering capacity, providing suitable soil pH a few months after application. Moreover, biochar induced woody plant finer roots development and significantly promoted root length, number of root forks, and crossings, while decreasing root average diameter. Conclusions Pinewood biochar significantly improved soil physical properties by moderating soil thermal properties, buffering soil pH, improving soil WHC, decreasing soil bulk density, and increasing soil porosity. In addition, biochar also strengthened the root architecture by improving root length, number of root forks, and crossings. Furthermore, roots from the amended treatment had longer root length with less average diameter than unamended roots, indicating that biochar may stimulate muscadine fine root development. The incorporation of biochar in soil enhanced woody plant root growth and development improved soil structure in sandy soils. It could potentially be a good strategy to tackle water loss, particularly in sandy soils.